2019
DOI: 10.1111/nph.15669
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species‐mediatedBIN2 activity revealed by single‐molecule analysis

Abstract: Summary Much evidence has shown that reactive oxygen species (ROS) regulate several plant hormone signaling cascades, but little is known about the real‐time kinetics and the underlying molecular mechanisms of the target proteins in the brassinosteroid (BR) signaling pathway. In this study, we used single‐molecule techniques to investigate the true signaling timescales of the major BR signaling components BRI1‐EMS‐SUPPRESSOR 1 (BES1) and BRASSINOSTEROID INSENSITIVE 2 (BIN2) of Arabidopsis thaliana. The rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Several posttranslational modifications also affect the activity of BIN2. HISTONE DEACETYLASE6 (HDA6) deacetylates BIN2, thereby repressing its kinase activity (Hao et al, 2016), whereas BIN2 is activated via oxidation at specific Cys residues (Song et al, 2018b). Dephosphorylation by RELATED TO ABSCISIC ACID INSENSITIVE1 (ABI1) and ABI2 (which negatively regulate abscisic acid [ABA] signaling) activates BIN2 in the presence of ABA (Wang et al, 2018a;Jiang et al, 2019).…”
Section: Activation Of Br Signalingmentioning
confidence: 99%
“…Several posttranslational modifications also affect the activity of BIN2. HISTONE DEACETYLASE6 (HDA6) deacetylates BIN2, thereby repressing its kinase activity (Hao et al, 2016), whereas BIN2 is activated via oxidation at specific Cys residues (Song et al, 2018b). Dephosphorylation by RELATED TO ABSCISIC ACID INSENSITIVE1 (ABI1) and ABI2 (which negatively regulate abscisic acid [ABA] signaling) activates BIN2 in the presence of ABA (Wang et al, 2018a;Jiang et al, 2019).…”
Section: Activation Of Br Signalingmentioning
confidence: 99%
“…Protein S-sulfenylation can directly regulate protein functions. For instance, in Arabidopsis, H 2 O 2 -dependent S-sulfenylation of BRASSINAZOLE-RESISTANT 1 (BZR1) promotes its interaction with transcriptional factors (TFs) and drives gene expression (Tian et al, 2018), whereas, S-sulfenylation of BRASSINOSTEROID INSENSITIVE 2 (BIN2) enhances the formation of phosphorylated BRI1-EMS-SUPPRESSOR 1 (BES1), which cannot transport and bind TFs in nuclei, thereby decreasing brassinosteroid (BR) signaling outputs (Song et al, 2019). Another example is the impact on the levels of the auxin biosynthetic precursor tryptophan by S-sulfenylation of a tryptophan synthetase β subunit 1 (Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At the receptor level, the function of BRI1 can be post-translationally regulated by PUB12/13-directed ubiquitination, PP2A-mediated dephosphorylation, BKI1-mediated kinase inhibition, and BIK1-and BIR3-mediated competition for the coreceptor BAK1 [69][70][71][72][73]. At the BIN2 level, it has been reported that BIN2 is regulated by OCTOPUSor POLAR-mediated membrane sequestration, HDA6-mediated deacetylation, KIB1-mediated ubiquitination, TTL-enhanced interaction with BSU1, ABI1/2-mediated dephosphorylation, and ROS (reactive oxygen species)-mediated oxidation [74][75][76][77][78][79][80]. At the transcription level, it has been reported that PP2A phosphatases can promote BR signaling by dephosphorylating BES1 and BZR1, whereas 14-3-3 and BRZ-SENSITIVE-SHORT HYPOCOTYL1 (BSS1) negatively regulate BR signaling by inhibiting the translocation of BES1 and BZR1 from the cytosol to the nucleus [81][82][83].…”
mentioning
confidence: 99%